Analisis Strategi Peningkatan Daya Tarik Toko Kue Solim Dengan Menggunakan Corerespondence Analysis - Mutiara Citra Sari; Dhea Sri Amanda; Suryatman Desri (Universitas 45 Surabaya, 2023)
This research aims to analyze the strategies for enhancing the attractiveness of Solim Cake Shop using the Correspondence Analysis method. Solim Cake Shop is a micro, small, and medium enterprise (MSME) that focuses on the production and sale of various types of cakes. In an effort to improve the standard of living for the community and compete with rival stores, this study is conducted to identify the position of Solim Cake Shop's products in terms of attributes desired by the public. The results of this research show that Solim Cake Shop has more advantages compared to other competitors.